Istirātījiyyāt Tadrīs al-Qawāid bi Ma’hadi Nur as-Salām Pamekasan Madura - Syamsul Arifin (Lisanudhad: Jurnal Bahasa, Pembelajaran dan Sastra Arab, 2021)
Arabic language learning encompasses four fundamental language skills—listening, speaking, reading, and writing—which are closely interconnected with linguistic components such as grammar (qawāʿid). Grammar serves as the foundation for understanding Arabic texts accurately and plays a crucial role in developing students’ overall language proficiency, particularly in reading and interpreting classical Arabic texts. Therefore, effective grammar instruction requires appropriate teaching strategies that correspond to students’ learning needs and the characteristics of the instructional materials. This study was motivated by the limited attention given to grammar learning strategies at Nurus Salam Islamic Boarding School, Pamekasan, Madura. Although vocabulary acquisition is essential, mastery of grammatical structures is equally important for enabling students to comprehend Arabic texts correctly. Accordingly, this study aims to (1) describe the grammar teaching strategies implemented at Nurus Salam Islamic Boarding School and (2) examine the functions of these strategies in supporting students’ Arabic language learning. A qualitative descriptive approach was employed in this research. Data were collected from the head of the boarding school, Arabic language teachers, and students through participatory observation, focused interviews, and document analysis. The collected data were analyzed using the interactive model of Miles and Huberman, which includes data reduction, data display, and conclusion drawing. The findings reveal that grammar instruction at Nurus Salam Islamic Boarding School utilizes five main strategies: the inductive method, the deductive method, the grammar–translation method, memorization, and continuous evaluation. These strategies contribute to improving students’ understanding of grammatical concepts, increasing learning efficiency, reducing students’ learning difficulties and lack of motivation, assisting teachers in delivering instructional materials more effectively, and creating a more efficient and structured learning process. The study concludes that the implementation of appropriate grammar teaching strategies significantly enhances the effectiveness of Arabic language instruction and facilitates students’ mastery of Arabic grammar.